Occupational therapists experiences of implementing a new complex intervention in collaboration with researchers: a qualitative longitudinal study. (4th March 2017) - Eriksson, Christina; Erikson, Anette; Tham, Kerstin; Guidetti, Susanne
Abstract: Background: This study was conducted in the context of a randomized controlled trial where occupational therapists (OTs) in collaboration with researchers implemented a client-centred activity of daily living intervention (CADL) for persons with stroke. Objective: The aim was to identify and describe over time the OTs' experiences regarding the collaboration with the researcher in their role as implementers of a new complex intervention. Method: Focus group interviews were conducted with 33 OTs, two, six and 12 months after they had participated in a five-day workshop. The interviews were analysed using a grounded theory approach. Results: Three categories were identified: (1) Including in the scientific world, (2) Involving as an implementer of science and (3) Integrating in a partnership. One core category emerged: The implementation of client-centred intervention enabled the fusion of practice and science. An increased experience of using CADL and support from the researchers changed the OTs' attitudes towards engaging in research from being an outsider to the scientific world to being included and then becoming a part of the research as an implementer of science. Conclusions: To create a context built on a collaborative partnership between practitioners and researchers enabled the fusion of practice and science.